2021
DOI: 10.2138/am-2021-7541
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence for the Fe3+ spin transition in iron-bearing δ-AlOOH at high pressure

Abstract: δ-AlOOH has emerged as a promising candidate for water storage in the lower mantle and could have delivered water into the bottom of the mantle. To date, it still remains unclear how the presence of iron affects its elastic, rheological, vibrational, and transport properties, especially across the spin crossover. Here, we conducted high-pressure X-ray emission spectroscopy experiments on a δ-(Al0.85Fe0.15) OOH sample up to 53 GPa using silicone oil as the pressure transmitting medium in a diamond-anvil cell. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Modeling of mid-ocean ridge basalt (MORB) hydration by formation of phases in the (δ-AlOOH)-(MgSiO 2 (OH) 2 )-(ε-FeOOH) solid solution may result in increased seismic velocities of hydrous MORB relative to pyrolytic mantle just below the mantle transition zone (∼680-900 km; Satta et al, 2021). However, the ν p and ν s values constrained for δ-(Al 0.97 Fe 0.03 )OOH and used in the modeling for seismic velocities of this solid solution are significantly faster than those constrained for compositions with greater concentrations of Fe: (δ-(Al 0.87 Fe 0.13 )OOH; Ohira et al (2021), (Al 0.956 Fe 0.044 )OOH; Su et al, 2021a;Su et al, 2021b). Comparison of sound velocities predicted by these studies reveal a decrease in both ν p and ν s with increasing Fe concentration, complicating the modeled seismic signature of MORB hydration and highlighting the need for additional measurements of sound velocities of compositions in the (δ-AlOOH)-(MgSiO 2 (OH) 2 )-(ε-FeOOH) solid solution.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Modeling of mid-ocean ridge basalt (MORB) hydration by formation of phases in the (δ-AlOOH)-(MgSiO 2 (OH) 2 )-(ε-FeOOH) solid solution may result in increased seismic velocities of hydrous MORB relative to pyrolytic mantle just below the mantle transition zone (∼680-900 km; Satta et al, 2021). However, the ν p and ν s values constrained for δ-(Al 0.97 Fe 0.03 )OOH and used in the modeling for seismic velocities of this solid solution are significantly faster than those constrained for compositions with greater concentrations of Fe: (δ-(Al 0.87 Fe 0.13 )OOH; Ohira et al (2021), (Al 0.956 Fe 0.044 )OOH; Su et al, 2021a;Su et al, 2021b). Comparison of sound velocities predicted by these studies reveal a decrease in both ν p and ν s with increasing Fe concentration, complicating the modeled seismic signature of MORB hydration and highlighting the need for additional measurements of sound velocities of compositions in the (δ-AlOOH)-(MgSiO 2 (OH) 2 )-(ε-FeOOH) solid solution.…”
Section: Discussionmentioning
confidence: 97%
“…The onset of the spin transition at a lower pressure in δ-(Al, Fe)OOH (32-40 GPa) compared to ε-FeOOH led Ohira et al (2019) to infer that the spin transition pressure in the (δ-AlOOH)-(ε-FeOOH) solid solution would increase with increasing iron concentration, an effect confirmed via Raman spectroscopy (Su et al, 2021a;Su et al, 2021b) and also observed for varying concentrations of Fe 2+ in (Mg, Fe)O (Fei et al, 2007b;Lin et al, 2005;Solomatova et al, 2016). Nishi et al (2019) observed a spin crossover of Fe 3+ at approximately 46 GPa in δ-(Al, Fe)OOH with Fe/(Al + Fe) = 0.23 and Fe/(Al + Fe) = 0.67.…”
Section: Comparison To Previous Studiesmentioning
confidence: 98%
“…The pressure-induced spin transition of iron greatly changes the chemical bonding of relevant minerals and thus, affects thermodynamic properties, rheology, and the thermal and electrical conductivity of iron-bearing minerals [Lin et al, 2013]. The iron spin transition occurs widely in the deep mantle for both iron-bearing oxide-hydroxides and metallic compounds [Lin et al, 2004a;Lin and Tsuchiya, 2008;Gu et al, 2014;Chen et al, 2018;Su et al, 2021]. At ambient conditions, the 3d-orbit electrons of Fe in all iron nitrides are in a high-spin ferromagnetic arrangement [Sifkovits et al, 1999].…”
Section: Introductionmentioning
confidence: 99%